Combined transbasal and transfacial approach - 山下, 敏夫; 辻, 弘之; 山内, 康雄; 久徳, 茂雄; 河本, 圭司; 吉村, 晋一; 川上, 勝弘; 沼, 義博; 藤沢, 琢朗; 細田, 泰男; 小川, 豊 (Oncologyの進歩, 1997)
Our institution routnely employs combined transbasal and transfacial approach for the resection of malignant tumors involving anterior cranial fossa. However, the extent of osteotomy and resection differs depending on the tumor invasion. We classified extent of osteotomy into 3 types. The operative mode wherein only the anterior cranial fossa is resected en bloc is defined as Type A, the operative mode wherein the tumor is resected en bloc together with the orbital contents is defined as Type B, the operative mode wherein the tumor is resected en bloc with the maxillary arch in addition to the orbital contents is defined as Type C. The 51-year-old female was admitted because of long lasting nasal bleeding. Magnetic Resonance Imaging (MRI) demonstrated the tumor which was located in the ethomoidal sinus. Brain and orbit were not involved. We chose Type A in the present case. Postoperative course is uneventful. These operative mode are useful in skull base surgery.